Cnoty główne w dyskusjach publicznych - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The discussions showed that society always practices or realizes moral virtues to an imperfect degree. The values that are associated with individual virtues are also objective in nature, and the social order prompts us to strive for their implementation.The analysed public discussions showed that man asks questions about moral values and obligations, about boundaries to protect these values. In society, there is more or less a conviction that respecting moral virtues ensures an internal and stable principle of society`s operation. They protect against dehumanizing tendencies and antisocial actions.
Keywords: cnota; dyskusja publiczna; etyka; moralność; virtue; public discussion; ethics; morality